Atypical clinical presentations of mastocytosis in children - Lange, Magdalena; Gwiazdowska, Anetta; Chylicka, Joanna; Żawrocki, Anton; Nedoszytko, Bogusław (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Mastocytosis is a group of rare diseases characterized by abnormal growth of mast cells (MC) in the skin, bone marrow, liver, spleen and lymph nodes. In children cutaneous mastocytosis (CM) is the predominant form. Objective. Presentation of four atypical cases of childhood CM with various clinical manifestations to demonstrate the wide spectrum of skin lesions and MC mediator-related symptoms and discuss indications to perform diagnostic procedures for systemic mastocytosis (SM) in children. Case reports. We describe the clinical presentation and diagnostic procedures performed in 3 girls and 1 boy aged from 9 month to 6 years. Disseminated CM with bullous lesions, large mastocytoma, plaque type and nodular type of CM were diagnosed. Elevated serum tryptase level and severe MC mediator-related symptoms were present only in a girl with extensive skin involvement and periodic blistering. SM or anaphylactic shock in the case history were not present in our children. Conclusions. Atypical clinical manifestations in infants and small children make the diagnosis of CM difficult. Initial diagnosis of SM, follow-up and prevention of anaphylaxis are recommended in paediatric mastocytosis cases.